Pengaruh Teknologi Terhadap Kinerja Pegawai Di Lembaga Pemasyarakatan Kelas IIA Bengkulu - Yolanda Nur Hafifa; Padmono Wibowo (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The utilization of information technology in a correctional facility (Lapas) is growing more crucial in the present digital age. This research aims to find out how much employee performance is influenced by technology at the Class IIA Bengkulu Correctional Institution. This research used quantitative methods with 35 people as samples. In collecting data, this research uses a questionnaire as an instrument to collect data collected from Google forms and data obtained using SPSS 25. The findings of the study indicate that 85.2%, whereas the remaining 14.8% is accounted for by other factors.